Anti Ghulul Values in Educational Leadership: A Hadith Perspective and Its Application to Organisational Justice - Asih, Dianing Banyu; Sulhan, Mohammad (UIN Sunan Gunung Djati Bandung, 2024)
Leadership in Islamic educational institutions has an important role as a guide, director, and inspirer for the organization to achieve goals based on the values of the Qur'an and hadith. However, the practice of ghulul, or abuse of trust in the form of corruption, nepotism, and injustice, often poses a serious challenge in creating Islamic leadership with integrity. This study aims to explore the values of justice and anti-ghulul from the hadith perspective and formulate strategies for their implementation in Islamic education management. The results show that the principles of trustworthiness, justice, and accountability in the hadith can be a solid basis for preventing ghulul and increasing efficiency, trust, and harmony in Islamic education organizations. The strategies formulated include strengthening the internal monitoring system, transparency in resource management, and creating a fair organizational culture based on meritocracy. The study concludes that the application of anti-ghulul values can integrate morality and spirituality into organizational governance, creating leadership that is oriented towards justice and sustainability. The findings provide theoretical contributions to the Islamic education management literature and practical guidance for leaders of educational institutions to build a management system with integrity. However, this research is limited to literature analysis, so further empirical studies are needed to test the relevance of these values in a broader context